1996
DOI: 10.1073/pnas.93.22.12445
|View full text |Cite
|
Sign up to set email alerts
|

Cell stress-regulated human major histocompatibility complex class I gene expressed in gastrointestinal epithelium.

Abstract: Conventional major histocompatibility complex (MHC) class I genes encode molecules that present intracellular peptide antigens to T cells. They are ubiquitously expressed and regulated by interferon y. Two highly divergent human MHC class I genes, MICA and MICB, are regulated by promoter heat shock elements similar to those ofHSP70 genes. MICA encodes a cell surface glycoprotein, which is not associated with f82-microglobulin, is conformationally stable independent of conventional class I peptide ligands, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

22
853
3
23

Year Published

2001
2001
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 940 publications
(901 citation statements)
references
References 51 publications
22
853
3
23
Order By: Relevance
“…The MIC gene transcriptional regulatory sequences contain heat-shock elements similar to those in the human Hsp70 promoter. Since genotoxic chemotherapeutic agents such as alkylating, cytotoxic, antimitotic and antimetabolic substances, activate the Hsp70 promoter (Hunt and Morimoto, 1985;Groh et al, 1996) via binding of HSF-1, thereby inducing gene transcription, similar mechanisms, may explain the induction of MIC-A/B expression by fotemustine (Liu et al, 1996). Though induction of MIC-A/B by chemotherapy and subsequent presence of an NKG2D þ inflammatory infiltrate was only investigated in one patient, our previous studies in cutaneous melanoma demonstrated changes in the inflammatory infiltrates at different tumour stages, which were associated with changes in MIC-A/B expression (Vetter et al, 2002), thus strengthening the relevance of these findings in this one patient.…”
Section: Loss Of Nonclassical Mhc Molecules Mic-a/b Expression Cs Vetmentioning
confidence: 99%
“…The MIC gene transcriptional regulatory sequences contain heat-shock elements similar to those in the human Hsp70 promoter. Since genotoxic chemotherapeutic agents such as alkylating, cytotoxic, antimitotic and antimetabolic substances, activate the Hsp70 promoter (Hunt and Morimoto, 1985;Groh et al, 1996) via binding of HSF-1, thereby inducing gene transcription, similar mechanisms, may explain the induction of MIC-A/B expression by fotemustine (Liu et al, 1996). Though induction of MIC-A/B by chemotherapy and subsequent presence of an NKG2D þ inflammatory infiltrate was only investigated in one patient, our previous studies in cutaneous melanoma demonstrated changes in the inflammatory infiltrates at different tumour stages, which were associated with changes in MIC-A/B expression (Vetter et al, 2002), thus strengthening the relevance of these findings in this one patient.…”
Section: Loss Of Nonclassical Mhc Molecules Mic-a/b Expression Cs Vetmentioning
confidence: 99%
“…4 MICA was thought to be normally expressed only in the gastrointestinal epithelium, 3 but it is possible that it occurs in every organ, except for the central nervous system. 5 Its expression is stress induced, similar to that of heat-shock protein 70, because of a putative heat-shock element in its 5 0 -untranslated region, 6 and it is commonly observed in tumors. 7,8 It binds to an activating receptor of natural killer (NK) cells, NKG2D, and interacts with gd T cells, NK cells and CD8 ab T cells.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Differently from other class I molecules, its expression does not depend on the presence of b2-microglobulin or ATP-binding cassette transporter TAP. 6,11 It may have an important role as a first line of defense in the epithelium signaling stressed cells to intraepithelial lymphocytes, but still much has to be learned about the functions of this gene.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Both the MIC genes (located on chromosome 6p21.3 12,13 ) and ULBP/RAET1 genes (positioned at 6q25 10 ) encode stress-inducible protein products, upregulated in malignant and virally infected cells and constitutively expressed within the epithelium of the gut. 10,11,14,15 The MIC-restricted Vd1 subset of gd T cells are the predominant lymphocyte present within intestinal epithelium. They require co-stimulation via NKG2D, 8 suggesting that the interaction of NKG2D with its ligands may play a role in shaping the immune response within the gut.…”
Section: Introductionmentioning
confidence: 99%